Volume-Based Thermoelasticity: Compressibility of Mineral-Structured Materials - Glasser, Leslie (American Chemical Society, 2010)
Thermodynamic properties, such as entropy among others, have been shown to correlate well with formula volume, thus permitting prediction of these properties on the basis of chemical formula and density alone, with no structural detail required. We here extend these studies to the thermoelastic property of isothermal compressibility of a wide range of materials. We show that compressibility is strongly linearly correlated with formula volume per atom pair, Vpr, within selected groups of materials (silicate clinopyroxenes, chalcopyrites, perovskites, transition metal diborides, spinels; these structurally related groups are selected on the basis of availability of experimental data). The groups are clearly distinguished by their "crumple" coefficients, w; that is, by the slopes of plots of their compressibilities versus their ion-pair volumes. The "crumple" coefficients decrease in the sequence of these groups listed above, and explanations are offered for the observed sequence: from flexible framework structures which crumple readily to rigid close-packed oxides and borides. This is believed to be the first examination of thermoelastic data across a wide range of structure groups, providing some broad insight into the factors influencing the elasticity of materials. The correlations may be used either to estimate or to check the compressibility of a material within a group.